Individuelle Autonome Fitness in Sport und Training - Reflexionen über ein neues Konzept in der Belastungssteuerung - Esperer, H. D.; Hottenrott, K. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
We introduced the concept of autonomic fitness (AFif), give a brief overview on the physlological basis of the parameters defining AFit, and discuss the potential value of AFit in the context of high performance endurance training. The autonomic nervous system is the main control system involved in the integration and coordination of the important reflexes arising in the various subsystems during the various phases of high performance training. Therefore, to monitor AFit parameters may prove superior to measuring solely the parameters of physical fitness. In fact, pre-liminary results from our group and others show that specific AFit parameters, such as Poincaré piot measures, yield information that is not obtained through the traditional measures of aerobic fitness (e. g. VO²max). We deem the AFit concept particulariy useful in the prescription of individually tailored training programs that are aimed at avoiding fatigue states, such as overreaching or overtraining. It is expected that the AFit concept will lead to a significant advancement of research in high performance training.